SPE Eastern Regional Meeting 2009
DOI: 10.2118/125944-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hydrajetting Applications in Horizontal Completions to Improve Hydraulic Fracturing Stimulations and Improve ROI

Abstract: This paper reviews applications of hydrajet perforating during the past 6+ years specifically as they apply to horizontal and highly deviated completions for both oil and gas reservoirs. Many benefits to hydraulic fracturing through hydrajetted perfs instead of shape charge perforations will often exist. Also, a key feature to more economic applications has been coupling this process with a method that includes multi-stage fracturing operations. This feature can shorten the completion time needed to achieve mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Additionally, external splash back only erodes an area on the thin outer shell that is inconsequential to the life of the inner carbide component of the tool where the jetting orifices are located. (McDaniel and Surjaatmadja, 2009). …”
Section: Advanced Abrasive Tool and Perforation Designmentioning
confidence: 99%
“…Additionally, external splash back only erodes an area on the thin outer shell that is inconsequential to the life of the inner carbide component of the tool where the jetting orifices are located. (McDaniel and Surjaatmadja, 2009). …”
Section: Advanced Abrasive Tool and Perforation Designmentioning
confidence: 99%
“…Hydra-jet multistage fracturing is a basic technology of horizontal well stimulation. Generally, there is no need to adopt a mechanical seal method; instead, one can rely on the highly concentrated and strong focus of dynamic fluid force [9]. It is a method that combines hydraulic sandblasting perforation, fracturing, and interval isolation in one technique according to the Bernoulli principle.…”
Section: Ct With Bot Packer Hydra-jet Multistage Fracturingmentioning
confidence: 99%
“…Some scholars focused on the application of a certain process in oil and gas reservoirs. Mcdaniel et al [9] reviewed applications of hydra-jet perforating in the years 2003-2009, particularly their practice on horizontal and highly deviated wells, and the research showed that hydra-jet perforating is widely used in horizontal wells, and that this technique is extremely superior in hard and very hard formations if high nozzle pressures are attained. Xiude et al [10] proposed a hydra-jet fracturing technology with bottom packer on coiled tubing, and they verified its successful application in low-permeability gas reservoirs in the Sichuan Basin, China.…”
Section: Introductionmentioning
confidence: 99%
“…Whether applied to open hole or cased hole completions, new techqniques have emerged within our industry to create multiple fractures via multiple treatment points along the completion interval in a single, continuous operation. Typical fracturing techniques include, but are not limited to, plug-and-perf (Blanton and Mackenzie, 2006), ball-actuated sleeves (Lohoefer et al, 2006;Snyder and Seale, 2011), coiled-tubing conveyed annular fracturing (Soliman et al, 2006;McDaniel and Surjaatmadja, 2009;Hari et al, 2010), and other hybrid methods, such as combinations of plug-and-perf and ball-actuated sleeves, RFID-actuated sleeves, abrasive sand jetting, and improved ball-actuated sleeves. Likewise, fluid diversion is achieved via composite bridge/frac plugs, external packers (either mechanical or swellables), coiled tubing re-settable packers, frac balls, and sand plugs.…”
Section: Introductionmentioning
confidence: 99%